2014
DOI: 10.1177/1355819614558472
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of systemic influences on paramedic decision making: care transitions and patient safety

Abstract: Objectives: Paramedics routinely make critical decisions about the most appropriate care to deliver in a complex system characterized by significant variation in patient case-mix, care pathways and linked service providers. There has been little research carried out in the ambulance service to identify areas of risk associated with decisions about patient care. The aim of this study was to explore systemic influences on decision making by paramedics relating to care transitions to identify potential risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
164
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(178 citation statements)
references
References 15 publications
7
164
0
7
Order By: Relevance
“…Another factor found within this theme was making use of a ‘feedback loop’. When EMS staff were provided with objective feedback information on non-conveyance responses, their self-motivation to improve care increased,48 63 and this led to individual and organisational learning 63. Under the workload theme, two studies found that attending incidents during difficult or busy shifts, or at the end of a shift, led to taking the easy option of conveying the patient to hospital 61 62…”
Section: Resultsmentioning
confidence: 99%
“…Another factor found within this theme was making use of a ‘feedback loop’. When EMS staff were provided with objective feedback information on non-conveyance responses, their self-motivation to improve care increased,48 63 and this led to individual and organisational learning 63. Under the workload theme, two studies found that attending incidents during difficult or busy shifts, or at the end of a shift, led to taking the easy option of conveying the patient to hospital 61 62…”
Section: Resultsmentioning
confidence: 99%
“…38 The focus on urgent care in this and in Sujan and colleagues' study is welcome as an example of a complex system or web of systems, providing an antidote to the dominance in previous research of studies within hospitals or single organisations. O'Hara and colleagues' study of decision making on ambulances, using immersive ethnographic methods, from observation of ambulance shifts to digital diaries held by paramedics, provides important insights into the complexity of decisions made by frontline staff.…”
Section: What These New Studies Addmentioning
confidence: 99%
“…The Consolidating Framework for Implementation Research24 offers insights into the conditions under which new interventions are and are not likely to be successfully implemented. It highlights that a ‘tension for change’ is one condition that facilitates successful uptake and implementation, that is, stakeholders need to perceive the current situation as needing to change and so be receptive to arrival of the new intervention 24.…”
Section: Discussionmentioning
confidence: 99%
“…It highlights that a ‘tension for change’ is one condition that facilitates successful uptake and implementation, that is, stakeholders need to perceive the current situation as needing to change and so be receptive to arrival of the new intervention 24. An older study looking at UK paramedics' willingness to undertake professional development more generally had suggested paramedics might be resistant to invest in their own development 25.…”
Section: Discussionmentioning
confidence: 99%